2018
DOI: 10.1002/anie.201809400
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Driven, Copper‐Catalyzed Decarboxylative C(sp3)−H Alkylation of Glycine and Peptides

Abstract: Despite a well‐developed and growing body of work in Cu catalysis, the potential of Cu to serve as a photocatalyst remains underexplored. Reported herein is the first example of visible‐light‐induced Cu‐catalyzed decarboxylative C(sp3)−H alkylation of glycine for preparing α‐alkylated unnatural α‐amino acids. It merits mentioning that the mild conditions and the good functional‐group tolerance allow the modification of peptides using this method. The mechanistic studies revealed that a radical–radical coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
86
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 180 publications
(87 citation statements)
references
References 79 publications
1
86
0
Order By: Relevance
“…In the past few years, with the rapid development of photoinduced radical reactions, the transition metal catalyzed photoredox radical–radical cross‐coupling has become a practical way for construction of C(sp 3 )−C(sp 3 ) bonds . We recently disclosed the first example of photoinduced Cu‐catalyzed alkylation of glycine C(sp 3 )−H for preparation of unnatural α‐amino acids and modification of peptides by decarboxylative cross‐coupling of alkyl N ‐hydroxyphthalimide esters (Scheme a) . Despite this progress, the transition‐metal‐free or catalyst‐free strategy for this transformation is highly desirable and still not realized.…”
Section: Methodsmentioning
confidence: 99%
“…In the past few years, with the rapid development of photoinduced radical reactions, the transition metal catalyzed photoredox radical–radical cross‐coupling has become a practical way for construction of C(sp 3 )−C(sp 3 ) bonds . We recently disclosed the first example of photoinduced Cu‐catalyzed alkylation of glycine C(sp 3 )−H for preparation of unnatural α‐amino acids and modification of peptides by decarboxylative cross‐coupling of alkyl N ‐hydroxyphthalimide esters (Scheme a) . Despite this progress, the transition‐metal‐free or catalyst‐free strategy for this transformation is highly desirable and still not realized.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, one feasible way is to activate the carboxylic acids and alkyl primary amines to the corresponding redox-active esters (RAE) and Katritzky's N-alkylpyridinium salts, respectively 16,17 . Previous studies demonstrated that both RAE [18][19][20][21][22][23][24][25][26][27][28] and Katritzky's salts [29][30][31][32][33][34][35][36][37] are predisposed to accept an electron from low-valent transition metals or organic Lewis bases under photocatalytic reaction conditions, thereby acting as precursors to the corresponding alkyl radicals (Fig. 1b) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] .…”
mentioning
confidence: 99%
“…In 2018, Wang, Xu, and co-workers described the reductive decarboxylative alkylation of glycine and glycine-containing peptides using an in situ-formed heteroleptic copper complex, [Cu(I)(dmp)(xantphos)]PF 6 (Scheme 25) [40]. Under blue light irradiation, glycine esters were readily alkylated using NHP esters in the presence of DABCO as a base.…”
Section: Reduction Reactionsmentioning
confidence: 99%